1980
DOI: 10.1177/0013916580121001
|View full text |Cite
|
Sign up to set email alerts
|

The Soft Classroom

Abstract: Most college students and faculty regard their classrooms as drab, sterile, and institutional. A traditional classroom was converted into a softer more aesthetically pleasing room. Student attitudes toward the new room were favorable, and there was an increase in classroom participation, including student-student discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 3 publications
1
18
0
1
Order By: Relevance
“…Special studies are concerned with special topics, for example large and small schools (Barker & Gump, 1964), open versus traditional schools (Gump, 1974), "soft classroom" (Sommer & Olsen, 1980), the school and classroom climate (Anderson, 1982;Arbinger & von Saldern, 1982;von Saldern, 1992), and the lab school Bielefeld (Schmittmann, 1985).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special studies are concerned with special topics, for example large and small schools (Barker & Gump, 1964), open versus traditional schools (Gump, 1974), "soft classroom" (Sommer & Olsen, 1980), the school and classroom climate (Anderson, 1982;Arbinger & von Saldern, 1982;von Saldern, 1992), and the lab school Bielefeld (Schmittmann, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies agree that seats in the middle of the classroom, facing the front, seem to be associated with better performance and participation (Becker, Sommer, Bee, & Oxley, 1973;Sommer, 1972;cf. Bell, Greene, Fisher, & Baum, 2001, p. 263 et sqq.).…”
Section: 83mentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have been undertaken that examine particular experiences, such as the increased student participation noted when a classroom was changed from straight rows of desks facing the teacher to one furnished with soft furnishings in a circular arrangement (Sommer & Olsen, 1988). Evidence of larger scale outcomes of educational facility design, however, remains difficult to gather (Lee & Tan, 2011;Woolner, Hall, Higgins, McCaughey, & Wall, 2007).…”
Section: Evidence In Educational Contextsmentioning
confidence: 99%
“…In addition, there are some limited suggestions that some individuals might be more sensitive to noise than others (Zimmer & Ellermeier, 1999;Belojevic et al, 2001). Maslow and Mintz (1956) found that participants in an 'ugly' room made significantly less positive judgements about photographs than did the participants doing the same task in a 'beautiful' room and it is clear that the provision of new buildings or the renovation of old ones can have marked effects (Sommer & Olsen, 1980;Berry, 2002) on motivation and engagement. However, it is likely that these effects tend to be short term, based on the initial 'wow factor' and if each cohort of users does not have the opportunity to personalise or 'own' the space, a decline in engagement would be expected.…”
Section: Colourmentioning
confidence: 99%